Design of PID controllers for dead-time systems using simulated annealing algorithms. (1st October 2010) - Kanthaswamy, G.; Jerome, Jovitha
The method of simulated annealing (SA)-based optimisation provides a non-oscillatory bounded solution closed-loop response for a large class of optimisation problems. The idea is to find a proportional-integral-derivative (PID) controller setting based on minimisation of cost function that makes the response from the set point to plant output as close as possible. In this paper, the performance of a PID controller designed using the SA, directed search SA based search-based simulated annealing (HPSSA) algorithmson simplex simulated annealing, heuristic pattern are exhaustively discussed and the results are found promising compared to the earlier non-heuristic methods proposed by Kookos and George Syrcos; Luyben; Visioli; and Chidambaram.